Osteochondritis Dissecans Involving the Trochlear Groove Treated With Retrograde Drilling: A Case Report. Issue 36 (September 2015) - Kaji, Yoshio; Nakamura, Osamu; Yamaguchi, Konosuke; Yamamoto, Tetsuji
Abstract : Abstract: Osteochondritis dissecans (OCD) occurs frequently in the humeral capitellum of the upper extremity, whereas OCD involving the trochlear groove (trochlear groove OCD) is rarely reported. A standard treatment for trochlear groove OCD has therefore not been determined, although several methods have been tried. The case of a 14-year-old male gymnast with bilateral trochlear groove OCD is presented. Retrograde drilling from the lateral condyle of the humerus was applied for the OCD lesion of the left elbow, since it was larger in size than that in the right elbow and was symptomatic. Conversely, since the right lesion was small and asymptomatic, it was managed conservatively. After treatment, consolidation of the OCD lesions was observed in both elbows. However, the time to healing was shorter in the left elbow treated surgically than in the right elbow managed conservatively. In conclusion, retrograde drilling is a very simple and minimally invasive treatment. This case suggests that retrograde drilling for trochlear groove OCD may be a useful procedure that may accelerate the healing process for OCD lesions.